2011
DOI: 10.1590/s1983-14472011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de pacientes com câncer de mama em terapia adjuvante

Abstract: RESUMOO objetivo do estudo foi avaliar a Qualidade de Vida (QV), identificar os domínios afetados em pacientes com câncer de mama em terapia adjuvante e correlacioná-los com características sócio-demográficas, clínicas e terapêuticas. Estudo transversal, realizado com 35 pacientes entre agosto de 2007 e dezembro de 2008. Utilizou-se o instrumento Quality of Life Core-30-Questionnaire (QLQ-C30). A Qualidade de Vida geral foi considerada pouco satisfatória. Os domínios afetados foram: função emocional, insônia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
19
1
27

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 13 publications
7
19
1
27
Order By: Relevance
“…Agreeing with the data in another study of 14 women who had mastectomies in Fortaleza, he showed that most of them said adherents of the Catholic religion, totaling 92.9%. [9][10][11] Regarding family history, it is stated that family history contributes to the increased risk of developing breast cancer two to three times, confirming the findings of the research. 12 Therefore, it may have been a major risk factor for the development of this neoplasia in interviewed, since most of them said that there were cases of breast cancer in their family.…”
Section: Discussionsupporting
confidence: 65%
“…Agreeing with the data in another study of 14 women who had mastectomies in Fortaleza, he showed that most of them said adherents of the Catholic religion, totaling 92.9%. [9][10][11] Regarding family history, it is stated that family history contributes to the increased risk of developing breast cancer two to three times, confirming the findings of the research. 12 Therefore, it may have been a major risk factor for the development of this neoplasia in interviewed, since most of them said that there were cases of breast cancer in their family.…”
Section: Discussionsupporting
confidence: 65%
“…The nurses should make sure to make the language easy to understanding, facilitating communication and aiming for its understanding. (15) The increase in the mean pain score was found in all BPI variables when comparing the first with the second and third assessments. In the univariate analysis, a correlation was found between pain intensity and interference in all daily activities in the BPI during the second assessment (p<0.05).…”
Section: Discussionmentioning
confidence: 87%
“…About emotional function, which figures in the functional scale of QLQ C30, low mean values were found in the three stages of the present study, which denotes that the women were emotionally worried, fearful and weakened during the whole treatment. In another study conducted in Porto Alegre about QL in women with breast neoplasia undergoing chemotherapeutic treatment, authors found changes in emotional function, signaling the impact that therapy had on this domain and on the QL of the affected women (Nicolussi & Sawada, 2011). Corroborating, authors observed in their findings that the worst QL levels were related to the emotional function, referring to the presence of irritation, depression, tension or worry among the women (Miranda, Neves, Costa, & Souza, 2013).…”
Section: Resultsmentioning
confidence: 99%